2013
DOI: 10.1038/jp.2013.129
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal isolated rectal bleeding and the risk of hypersensitivity syndromes

Abstract: An IRB event in the neonatal period does not increase the risk of developing hypersensitivity syndromes or food allergies during childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(17 reference statements)
1
3
0
Order By: Relevance
“…Our findings are in line with previous studies suggesting that the lack of breast milk has been significantly associated with IRB 1‐4 . Evidence suggested that a shorter period of breastfeeding was a significant predictor for IRB 1‐4 5 …”
Section: Variables Cases (N=71) Controls (N=281) Psupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings are in line with previous studies suggesting that the lack of breast milk has been significantly associated with IRB 1‐4 . Evidence suggested that a shorter period of breastfeeding was a significant predictor for IRB 1‐4 5 …”
Section: Variables Cases (N=71) Controls (N=281) Psupporting
confidence: 93%
“…Our findings are in line with previous studies suggesting that the lack of breast milk has been significantly associated with IRB. [1][2][3][4] Evidence suggested that a shorter period of breastfeeding was a significant predictor for IRB. [1][2][3][4] The alteration in the composition of the intestinal microbiome in formula-fed infants has been associated with an increase of pro-inflammatory bacterial taxa and intestinal permeability, which could explain the clinical appearance of rectal bleeding.…”
Section: B R I E F R E P O R T Neonatal Isolated Rectal Bleeding: a Case-control Studymentioning
confidence: 99%
See 2 more Smart Citations